Application of different hardware and software in the concept of digital pilot training and selection - Knežević, Aleksandar Z.; Bukvić, Aleksandar G.; Krstić, Branimir B. (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: In many military air forces and civil aviation organizations that use or own training aircraft equipped with a digital cockpit, training tools such as trainers and simulators are understood to a varying extent. Special attention is paid to the ratio of hours spent training on the real aircraft to the number of hours spent on the simulator. This approach in training professional circles and the public is called Live virtual constructive. For all other teaching aids used for preparation for training, neither the methodology nor the extent of their use has been specifically investigated. The research aims to develop instruments that will measure and evaluate the success and qualitative progress in pilot training achieved by using the digital cabin space, based on which a decision can be made about further training for a specific aircraft type. Methods: In conjunction with a PC-based aviation training device and advanced statistical analyses, an eye movement tracking device will help arrive at a reference pattern of instrument observation to train pilots and select pilot candidates.Results: The proposed concept's research includes detailed descriptions of the application of trainers and teaching aids with different profiles, which significantly impact the quality of the implementation of the digital cabin space in the training of cadet pilots.Conclusion: Given that the Military Academy educates cadet pilots who continue their training in the operational flying units of the Serbian Armed Forces (SAF), it is essential that during the period spent at the Military Academy, their quality theoretical preparation be carried out.
Keywords: flight training; simulation; hardware; software